2018
DOI: 10.1101/451591
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lipid unsaturation properties govern the sensitivity of membranes to photo-induced oxidative stress

Abstract: Unsaturated lipid oxidation is a fundamental process involved in different aspects of cellular bioenergetics; dysregulation of lipid oxidation is often associated with cell aging and death. In order to study how lipid oxidation affects membrane biophysics, we used a chlorin photosensitizer to oxidize vesicles of various lipid compositions and degree of unsaturation in a controlled manner. We observed different shape transitions that can be interpreted as an increase in the area of the targeted membrane followe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 60 publications
0
5
1
Order By: Relevance
“…S7a. In our observations, we found that vesicles increased their diameters by up to 2.5-fold which is much larger than a reported 4% expansion range for liposomes (which did not experience a Phoenix behavior) 54 . This can be explained by the presence of monomers and hydration within the bilayers of vesicles, which act as plasticizers in the membranes and thus provide more flexibility for the expansion of the lumen of the vesicles.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…S7a. In our observations, we found that vesicles increased their diameters by up to 2.5-fold which is much larger than a reported 4% expansion range for liposomes (which did not experience a Phoenix behavior) 54 . This can be explained by the presence of monomers and hydration within the bilayers of vesicles, which act as plasticizers in the membranes and thus provide more flexibility for the expansion of the lumen of the vesicles.…”
Section: Discussioncontrasting
confidence: 65%
“…3b, c, we show that both photocatalysts are indeed vulnerable to degradation when irradiated with blue light in an oxygen-rich environment, and show reductions in their absorbance peak intensities of 24 and 22% respectively. Furthermore, the hydrophilic oxidative products formed by the degradation of m-RAFT, Ru(bpy) 3 2+ and rhodamine 6 G are capable of rapidly dissolving into the water phase and thereby increase the osmotic solute concentrations 32,46,54 .…”
Section: Resultsmentioning
confidence: 99%
“…In our observations, we found that vesicles increased their diameters by up to 2.5-fold which is much larger than a reported 4% expansion range for liposomes (which did not experience a Phoenix behavior). 50 This can be explained by the presence of monomers and hydration within the bilayers of vesicles, which act as plasticizers in the membranes and thus provide more exibility for the expansion of the lumen of the vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…As predicted by the Rayleigh-Plesset equation for a "bubble", 60 when the vesicle reaches a critical expansion maximum size the membrane implodes and the inner aqueous solution leaks out to relax the expansion pressure. This relaxation, in turn, allows resealing of the membrane through the pore-line tension 50,61 around the surface defects and results in a smaller vesicle or droplet. The growth in size and implosion episodes proceed in a successive manner as photo-degradation and osmotic imbalance continue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation